1991
DOI: 10.1161/01.res.69.5.1171
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative effects due to calcium binding by troponin and their consequences for contraction and relaxation of cardiac muscle under various conditions of mechanical loading.

Abstract: A mathematical model for the regulation of mechanical activity in cardiac muscle has been developed based on a three-element rheological model of this muscle. The contractile element has been modeled taking into account the results of extensive mechanical tests that involved the recording of length-force and force-velocity relations and muscle responses to short-time deformations during various phases of the contraction-relaxation cycle. The best agreement between the experimental and the mathematical modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 26 publications
5
53
0
Order By: Relevance
“…6,A, B) [3]. This effect was earlier validated in our cellular model [5,7] incorporated now in the fiber model. The fiber model also proved to simulate this phenomenon correctly:…”
Section: Afterloaded Contractions In the 1d Fiber Modelsupporting
confidence: 72%
See 2 more Smart Citations
“…6,A, B) [3]. This effect was earlier validated in our cellular model [5,7] incorporated now in the fiber model. The fiber model also proved to simulate this phenomenon correctly:…”
Section: Afterloaded Contractions In the 1d Fiber Modelsupporting
confidence: 72%
“…Cooperative mechanisms of CaTnC kinetics as well as respective equations are identified and justified in our previous papers [5,8,24]. Thus, direct links and feedback between Ca 2+ kinetics, CEx deformations, and force generation are defined in the EO model and ensured from the cooperative mechanisms of myofilament Ca 2+ activation.…”
Section: +mentioning
confidence: 92%
See 1 more Smart Citation
“…It is not necessary to introduce length-dependent myofilament calcium affinity for the four-state model to explain contractile behavior on ejecting beats. Prior investigators advanced the concept of explaining whole heart behavior on the basis of the fundamental principles of muscle contraction (10,11,17,26). The present study represents another step toward this goal by offering a comprehensive explanation for load dependence of ventricular performance, thus advancing understanding of the physiology of the intact heart under physiological conditions.…”
Section: Discussionmentioning
confidence: 92%
“…Prior theoretical studies have shown that one or another model could in general explain contractile behavior during shortening (17,22), but there has been no prior attempt to explicitly test those models against measured data. The breadth of phenomena explained by the present model, however, should be acknowledged.…”
Section: Discussionmentioning
confidence: 99%